Factor Affecting Motivation Level Employee on Acquisition Strategy - Ismail, Fadillah; Mardhiyah Nor Aziz, Ainul; Md. Syukri Wan Mohamad Ali, Wan; Aisyah Panatik, Siti; Syereena Nojumuddin, Nur (International Journal of Engineering and Technology, 2018)
Most employees require motivation to like their employments and perform ideally. A few workers are cash motivated while others discover acknowledgment and rewards expressly inspiring. Motivation levels inside the working environment directly affect worker productivity. Workers who are inspired and amped up for their occupations do their duties to the level best of their capacity and productivity. Employee motivation has dependably been a focal issue for organization. Managers need to become more acquainted with their employee exceptionally well and utilize diverse strategies to propel each of them in light of their own needs. In this study, we would like to emphasis the objective on the importance factors of motivation in the workplace to improve the job satisfaction, organizational performance and productivity during acquisition strategy take place in the organization. Contribution of employees in management and decision making associated to policies, objectives and strategies of the organization and enhance further study for academia.
Keywords: Human Resource; Motivation Employee; Acquisition; Management